Prothrombin complex concentrates for perioperative vitamin K antagonist and non-vitamin K anticoagulant reversal - Levy, Jerrold; Steiner, Thorsten (Anesthesiology, 2018)
Vitamin K antagonist therapy is associated with an increased bleeding risk, and clinicians often reverse anticoagulation in patients who require emergency surgical procedures. Current guidelines for rapid anticoagulation reversal for emergency surgery recommend four-factor prothrombin complex concentrate and vitamin K coadministration. The authors reviewed the current evidence on prothrombin complex concentrate treatment for vitamin K antagonist reversal in the perioperative setting, focusing on comparative studies and in the context of intracranial hemorrhage and cardiac surgery. The authors searched Cochrane Library and PubMed between January 2008 and December 2017 and retrieved 423 English-language papers, which they then screened for relevance to the perioperative setting; they identified 36 papers to include in this review. Prothrombin complex concentrate therapy was consistently shown to reduce international normalized ratio rapidly and control bleeding effectively. In comparative studies with plasma, prothrombin complex concentrate use was associated with a greater proportion of patients achieving target international normalized ratios rapidly, with improved hemostasis. No differences in thromboembolic event rates were seen between prothrombin complex concentrate and plasma, with prothrombin complex concentrate also demonstrating a lower risk of fluid overload events. Overall, the studies the authors reviewed support current recommendations favoring prothrombin complex concentrate therapy in patients requiring vitamin K antagonist reversal before emergency surgery.